(untitled) (Journal of the College of Basic Education, 2026)
The subject of expressive levels is fertile ground for study and research, as it deals with various expressive mechanisms that mostly operate on the structural composition and expressive mood, as well as the visual composition of poetic text. Mufaq Muhammad is one of the Iraqi poets whose expressive system is distributed across various levels, from suggestion, symbolism and strangeness to expressive and emotional excitement, passing through the encryption of the expressive system and increasing the communicative charge up and down, depending on the enlightening power of the poet’s language and the level of expressive charge All of this is based on the structure and nature of the internal relationships within the text, highlighting the expressive turmoil in this composition through areas of illumination that are mostly connected to an emotional state stemming from the reality of Iraqi suffering caused by political, social and economic transformations and the accompanying changes in the deep structure of the society that forms the incubator that produced these texts.